(untitled) (Vietnam Journal of Community Medicine, 2026)
Background:Ketamine is a dissociative anesthetic that has been increasingly abused for recreational purposes. Ketamine-related urinary tract injury has been widely described; however, the presence of abnormalities involving multiple organs on computed tomography (CT) has not been fully reported in the literature.Case presentation:We report the case of a 34-year-old man who was admitted with prolonged fever, urinary frequency, and elevated liver enzymes. Intervention and course:Contrast-enhanced CT demonstrated hepatomegaly, arterial-phase hepatic perfusion abnormalities, and multiple small scattered hypoattenuating lesions within the liver. Additional findings included intrahepatic bile duct wall thickening with fusiform dilation of the common bile duct, as well as a small-capacity urinary bladder with diffuse wall thickening. Other associated abnormalities included small bowel wall thickening and bilateral adrenal enlargement. Follow-up CT after treatment showed improvement in hepatic parenchymal lesions and reduced perfusion abnormalities.Conclusion:These findings suggest multiorgan involvement associated with chronic ketamine abuse and highlight the role of multiphasic CT in identifying associated abnormalities and supporting diagnostic orientation.